Lancashire and the New Liberalism: A Half-century Retrospective. (1st January 2021) - Collinson, Marc
Abstract : This article reflects on the significance of P.F. Clarke's seminal Lancashire and the New Liberalism. It considers the book's influence on academic debates over the 'franchise factor' in Labour's displacement of the Liberal party, its influence on how we perceive Lancashire as an historical case study, and how it shaped subsequent interpretations of British political history. This short article is hopefully the first in a new subcategory of retrospective essays for Transactions . These will reflect on a significant text affecting the historical study of Lancashire and Cheshire. Authors will draw out the key themes of the individual work and discuss their significance on subsequent historiographical debate and methodological practice. 1